ANALISIS PERSEPSI KONSUMEN TERHADAP KUALITAS PENDAP DI USAHA PENDAP & PALAI CIK SUR KOTA BENGKULU - Elsi Munalisa; Eti Arini (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze consumer perceptions of the product quality of Pendap at Usaha Pendap & Palai Cik Sur in Bengkulu City, identify the quality aspects that most influence consumer evaluations, and understand their relationship with purchase intention and loyalty. The research employs a qualitative method with a case study approach. Primary data were obtained through observation, in-depth interviews with 10 consumers and the business owner, as well as documentation. Data analysis was conducted using thematic analysis techniques to identify patterns in consumer perceptions. The results show that, in general, consumers have a positive perception of Pendap quality, particularly in terms of taste, texture, and cleanliness, which are considered distinctive, authentic, and consistent. However, there are critical notes regarding packaging and presentation aspects, which some consumers perceive as still simple, less informative, and less visually appealing. These findings align with consumer perception theory, which includes cognitive, affective, and conative dimensions, and emphasize the importance of packaging innovation and enhancing visual appeal without eliminating the product’s traditional values. This research is expected to contribute theoretically to the study of traditional culinary marketing and provide practical insights for MSME actors to improve competitiveness through product quality enhancement, particularly in visual and packaging aspects. Keywords: consumer perception, product quality, pendap, traditional food, Bengkulu